1994
DOI: 10.1039/jm9940400071
|View full text |Cite
|
Sign up to set email alerts
|

Helix inversion in the chiral nematic phase of a ferroelectric liquid crystal containing a single chiral centre

Abstract: An inversion in the cholesteric phase has been found to occur with change in temperature. Additionally, the material under investigation was found to exhibit unusual ferroelectric properties on cooling from the chiral nematic phase. We report the synthesis and physical properties, including pitch and polarization data, for (S)-4-noctyloxy-2,3-difluorobiphenyl-4'-yl 3-difluorobiphenyl-4'-yl 3-fluoro-4-(2-fluorooctanoyloxy)benzoate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 7 publications
3
20
0
1
Order By: Relevance
“…Upon cooling down to the N* phase from isotropic melt, (+)-S-1 exhibited a strong negative Cotton effect in the absorption region of p ‐terphenyl, implying the formation of a left‐handed helix 44. The intensity of the Cotton effect decreased with reducing temperature and finally inverses from negative to positive at the N* to TGBC* transition, implying that the handedness of (+)-S-1 inversed from left in the N* state to right in the TGBC* state through a non‐helical chiral LC phase 16–24. Although (+)-S-2 was similar to (+)-S-1 in structure, it displayed a positive Cotton effect in the N* phase, an implication of right‐handed helix formation.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Upon cooling down to the N* phase from isotropic melt, (+)-S-1 exhibited a strong negative Cotton effect in the absorption region of p ‐terphenyl, implying the formation of a left‐handed helix 44. The intensity of the Cotton effect decreased with reducing temperature and finally inverses from negative to positive at the N* to TGBC* transition, implying that the handedness of (+)-S-1 inversed from left in the N* state to right in the TGBC* state through a non‐helical chiral LC phase 16–24. Although (+)-S-2 was similar to (+)-S-1 in structure, it displayed a positive Cotton effect in the N* phase, an implication of right‐handed helix formation.…”
Section: Resultsmentioning
confidence: 97%
“…Later, Goodby et al13–15 found that the rule was also applicable to other liquid crystalline mesophases, like helicoidal smectics. More recent investigations have shown that, for certain types of chiral LCs, the twist sense also depends on temperature, which induces the change in the population of conformational isomers 16–24. For example, a thermotropic LC compound, 4″‐propoxymethylene‐2′‐fluoro‐4‐[(2 S , 3 S )‐3‐propyloxiran‐2‐ylmethoxy]‐[1,1′:4′,1″]terphenyl, exhibits a temperature‐dependent helix inversion in both the cholesteric (N*) and chiral smectic phases 22.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Die Molekülstrukturen einiger nematischer LCs zur Erzeugung von CLCs sind in Schema dargestellt. Es ist auch bekannt, dass CLCs eine Helixinversion in Abhängigkeit von der Temperatur eingehen können, allerdings sind diese Systeme nicht Thema dieses Aufsatzes. Es ist zu beachten, dass die temperaturinduzierte Chiralitätsumkehr von CLCs zwar von grundlegender wissenschaftlicher Bedeutung ist, potenzielle Anwendungen aber durch die erforderlichen hohen Temperaturen eingeschränkt sind.…”
Section: Lichtgesteuerte Chiralitätsumkehr In Helikalen Clc‐überstruunclassified
“…An interesting phenomena which is not too often observed is the so called cholesteric twist inversion [32][33][34][35][36]. While this is easily explained for mixtures of different components through a different temperature dependence of the pitch [37,38], it is much more surprising in a single component system.…”
Section: Propertiesmentioning
confidence: 99%